ELEMENTOS LEXICOGRÁFICOS E ENCICLOPÉDICOS NA DEFINIÇÃO TERMINOLÓGICA: QUESTÕES DE PARTIDA - Finatto, Maria José Bocorny (Organon, 2012)
This paper concerns the apprehension conditions of the nature and functioning of the terminologicaldefinition (TD) viewed beyond the genus proximum and differentia specifica categories. In this way, it suggestsperspectives to investigate the possible similarities between lexicographic and encyclopaedic definitions whichare presumably manifested on TDs. Drawing from the tendencies observed on environmental legal TDs, andfrom the features observed on definition samples collected from lexicographic, encyclopaedic and terminologicalworks, it discusses the application of the encyclopaedic tradition to the formulation of terminological definitions.